Cadherin 13: Human cis-Regulation and Selectively Altered Addiction Phenotypes and Cerebral Cortical Dopamine in Knockout Mice - Jana Drgonova; Donna Walther; G. Luke Hartstein; Mohammad O. Bukhari; Michael H. Baumann; Jonathan Katz; F. Scott Hall; Elizabeth R. Arnold; Shaun Flax; Anthony Riley; Olga Rivero; Klaus-Peter Lesch; et al. (BMC, 2016)
Abstract The Cadherin 13 (CDH13) gene encodes a cell adhesion molecule likely to influence development and connections of brain circuits that modulate addiction, locomotion and cognition, including those that involve midbrain dopamine neurons. Human CDH13 mRNA expression differs by more than 80% in postmortem cerebral cortical samples from individuals with different CDH13 genotypes, supporting examination of mice with altered CDH13 expression as models for common human variation at this locus. Constitutive CDH13 knockout mice display evidence for changed cocaine reward: shifted dose response relationship in tests of cocaine-conditioned place preference using doses that do not alter cocaine-conditioned taste aversion. Reduced adult CDH13 expression in conditional knockouts also alters cocaine reward in ways that correlate with individual differences in cortical CDH13 mRNA levels. In control and comparison behavioral assessments, knockout mice display modestly quicker acquisition of rotarod and water maze tasks, with a trend toward faster acquisition of 5-choice serial reaction time tasks that otherwise displayed no genotype-related differences. They display significant differences in locomotion in some settings, with larger effects in males. In assessments of brain changes that might contribute to these behavioral differences, there are selective alterations of dopamine levels, dopamine/metabolite ratios, dopaminergic fiber densities and mRNA encoding the activity dependent transcription factor npas4 in cerebral cortex of knockout mice. These novel data and previously reported human associations of CDH13 variants with addiction, individual differences in responses to stimulant administration and attention deficit hyperactivity disorder (ADHD) phenotypes suggest that levels of CDH13 expression, through mechanisms likely to include effects on mesocortical dopamine, influence stimulant reward and may contribute modestly to cognitive and locomotor phenotypes relevant to ADHD.